2004
DOI: 10.1038/oby.2004.254
|View full text |Cite
|
Sign up to set email alerts
|

Cut‐off Point of BMI and Obesity‐Related Comorbidities and Mortality in Middle‐Aged Koreans

Abstract: OH, SANG WOO, SOON-AE SHIN, YOUNG HO YUN, TAIWOO YOO, AND BONG-YUL HUH. Cut-off point of BMI and obesity-related comorbidities and mortality in middle-aged Koreans. Obes Res. 2004;12:2031-2040. Objective: The need for a lower BMI to classify overweight in Asian populations has been controversial. Using both disease and mortality outcomes, we investigated whether lower BMI cut-off points are appropriate for identifying increased health risk in Koreans. Research Methods and Procedures:We conducted a cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
122
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 26 publications
2
122
1
Order By: Relevance
“…On the other hand, the appropriateness of the BMI cutoffs in Asian populations, in spite of wide accepted application, has been questioned in recent years (Oh et al, 2004;WHO, 2004). Hence, it is prudent to make the diagnosis of obesity based on the measure of percentage body fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the appropriateness of the BMI cutoffs in Asian populations, in spite of wide accepted application, has been questioned in recent years (Oh et al, 2004;WHO, 2004). Hence, it is prudent to make the diagnosis of obesity based on the measure of percentage body fat.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the BMI classification of overweight and obesity in Asian populations has been controversial, and investigating whether the accepted BMI cutoff points are appropriate for identifying increased health risks is an important challenge for Asian countries health systems (Oh et al, 2004). A WHO (World Health Organization) expert consultation reviewed scientific evidence, which suggests that Asian populations have different associations between BMI, percentage of body fat and health risks than do European populations, and they concluded that the proportion of Asians with a high risk of type II diabetes and CVD is substantial at BMIs lower than existing WHO cutoff point for overweight (i.e., BMIX25 kg/m 2 ) (WHO, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…11 Some studies showed that Asians have lower BMI but higher PBF than Caucasians, and that some Asian population's morbidity and mortality of obesity-related diseases are relatively high at a relatively low BMI level. [12][13][14] From those perspectives, the WHO expert consultation recently reported that the universal BMI criteria for adult obesity are not suitable for Asian populations, although no recommendation for new, clear, BMI cutoff points was given for any Asian population. 15 From this perspective, variations in criteria among various ethnic populations should be considered in evaluating obesity in children.…”
Section: Discussionmentioning
confidence: 99%
“…1 In Japan, the prevalence of obesity has been consistently increasing in men, whereas it has been stable over the last 10 years in women, according to the annual reports of the National Nutrition Survey, Japan (NNS-J); currently, the prevalence of overweight is 30.9% in men and 22.7% in women aged 20 years or older. 2 As persons with overweight and obesity are at an increased risk of type 2 diabetes, hypertension and dyslipidemia, [3][4][5] there is an urgent need to establish strategies to prevent overweight and obesity. In Japan, the Ministry of Health and Welfare has initiated a project of Healthy Japan 21 to encourage changes in lifestyle, 6 and weight reduction is one of the major challenges of this project.…”
Section: Introductionmentioning
confidence: 99%